High‐frequency‐link DC solid state transformer based on voltage self‐balancing control for MVDC power distribution application - Peng Wang (Wiley, 2021)
Abstract This paper presents a novel voltage self‐balancing converter (VBC) applied to DC solid‐state transformer (DCSST), analyzes the operating principle of the proposed VBC, and proves the voltage balance performance. Based on this converter, a novel DCSST topology is proposed, which can be used in medium and low voltage DC distribution application, microgrid and medium and low voltage energy storage system. Compared with the previous work, under the same voltage level, it can effectively reduce the number of transformers and switches, reduce the voltage level of switches, and realize the soft switching of the VBC switches, so as to improve the system efficiency and power density, and then improve the system reliability. Meanwhile, the fault handling ability and fault tolerance ability of DCSST are improved, which makes DCSST more reliable when multiple isolated bi‐directional DC/DC Converters (IBDC) are connected in series. In addition, with this topology, the input voltage self‐balancing control strategy of the IBDC is not needed because of the voltage self‐balancing characteristic of VBC, which simplifies the control complexity and greatly improves the control accuracy of the control system. Experimental results agree well with the accuracy and correctness of the proposed topology.